Magnetically coupled Fano resonance of dielectric pentamer oligomer. (15th June 2017) - Zhang, Fuli; Li, Chang; He, Xuan; Chen, Lei; Fan, Yuancheng; Zhao, Qian; Zhang, Weihong; Zhou, Ji
Abstract: We present magnetically induced Fano resonance inside a dielectric metamaterial pentamer composed of ceramic bricks. Unlike previous reports where different sizes of dielectric resonators were essential to produce Fano resonance, under external magnetic field excitation, central and outer dielectric bricks with identical sizes exhibit in-phase and out-of-phase magnetic Mie oscillations. An asymmetric line shape of Fano resonance along with enhanced group delay is observed due to the interference between the magnetic resonance of the central brick and the symmetric magnetic resonance of outer bricks. Besides, Fano resonance blueshifts with the increasing resonance of the smaller central brick. The thermal-dependent permittivity of ceramics allows Fano resonance to be reversibly tuned by 300 MHz when temperature varies by 60 °C.